2004
DOI: 10.1080/14034910310019227
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, the miniaturization of community and assessment of patient satisfaction in primary healthcare: a population-based study

Abstract: Low levels of trust and the miniaturization of community may enhance non-specific patient dissatisfaction such as experience of lack of openness by the patient. In contrast, the miniaturization of community was not significantly associated with the more specific "lack of information". The results have implications for the evaluation of patient dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Trust and communication skills are considered as the main reason for patients' willingness to seek health care (Hall, Dugan, Zheng, & Mishra, 2001;Gilson, 2003, Russell, 2005, encouraging individuals to use services (Gilson, 2003;Russell, 2005), staying with a practice (Junod Perron, Favrat, & Vannotti, 2004), and are closely related to patient satisfaction and adherence to treatment (Birkel & Reppucci, 1983;Hall, Dugan, Zheng, & Mishra, 2001;Lindström & Axén, 2004). This study has found that even in a country such as Sweden, with universal access to health-care, poor trust in the health care system is significantly associated with poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…Trust and communication skills are considered as the main reason for patients' willingness to seek health care (Hall, Dugan, Zheng, & Mishra, 2001;Gilson, 2003, Russell, 2005, encouraging individuals to use services (Gilson, 2003;Russell, 2005), staying with a practice (Junod Perron, Favrat, & Vannotti, 2004), and are closely related to patient satisfaction and adherence to treatment (Birkel & Reppucci, 1983;Hall, Dugan, Zheng, & Mishra, 2001;Lindström & Axén, 2004). This study has found that even in a country such as Sweden, with universal access to health-care, poor trust in the health care system is significantly associated with poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…Esta não pretende ser uma revisão completa, visto que novas evidências aparecem rapidamente. Com relação à saúde vários níveis de análise têm sido propostos: (i) indivíduos ou domicílios 53,54,55,56,57,58,59,60,61,62,63,64,65 ; (ii) vizinhança ou bairros 51,66,67,68,69,70,71 ; (iii) regiões 72,73 ; (iv) Estados de um único país 74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91 ; e (v) entre países 92,93 .…”
Section: Relacionamento Entre Capital Social E Saúdeunclassified
“…There was also the problem of interpreting contradicting findings among the social capital variables examined. For example, where social capital variables were examined separately, 'trust' was often found to be significantly related to the outcome, but social participation variables were not (Lindström & Axén, 2004;Wan & Lin, 2003). This raises questions about the wisdom of combining these different types of variables (cognitive and structural or bonding and bridging) into a summary social capital scale, as was done in several of the articles reviewed.…”
Section: Disentangling the Effects Of Social Capitalmentioning
confidence: 99%